Sheltered by Stars: The Courtyard Essence in Indian Homes - Tejashree Kusuma (Institute for Research and Community Services Udayana University, 2026)
This paper addresses the decline of traditional courtyard architecture in modern urban contexts, which has led to a disconnect between architectural design, environmental sustainability, and social cohesion. The study employs a comparative analysis of traditional and modern courtyard homes, focusing on their design principles, climatic adaptations, cultural significance, and technological advancements. Case studies from regions like Rajasthan, Gujarat, and Tamil Nadu are examined to understand how traditional designs addressed climatic challenges and social needs. Traditional courtyards excelled in passive climate control, natural ventilation, and fostering community interaction. Modern interpretations integrate advanced materials and technologies, such as vertical gardens and solar systems, adapting these spaces for urban living while retaining core benefits. However, modern designs often prioritize privacy over communal aspects, reflecting evolving lifestyles. Courtyard architecture offers timeless solutions for sustainable living by balancing cultural values, environmental adaptation, and human well-being. Integrating traditional principles with modern innovations can bridge the gap between heritage and contemporary needs. The findings emphasize the potential of reimagined courtyard designs to address urban challenges like energy efficiency, social isolation, and environmental sustainability. This approach offers a framework for architects to create resilient, human-centric urban spaces that honor cultural heritage while addressing modern demands